Efektivitas Model Pembelajaran Biologi Berbasis Kearifan Lokal Effectiveness Biology Learning Model Based on Local Wisdom - Putri, Sonia; Darussyamsu, Rahmawati (Prosiding Seminar Nasional Biologi, 2021)
In learning, it is necessary to pay attention to learning models according to the conditions of students and the material. Biology is the study of living things. Success in learning according to several components, one of which is the learning model. An appropriate learning model is needed to achieve learning goals. One of the learning models that can be used in biology learning is a learning model based on local wisdom. This study aims to figure out more about the biology learning model based on local wisdom. The method used to achieve the goals of this research is a literature study. By carrying out this research is expected to increase the insight of teachers regarding biology learning models based on local wisdom and can be used as a consideration in designing appropriate learning models according to the material and conditions of students. Based on the results of the literature study obtained that the biology learning model based on local wisdom was effective implemented in learning. It could make it easier for students to understand the material, making the learning more meaningful and increase the students’ learning outcome.